Genus Mallotus (Euphorbiaceae): A review on traditional medicinal use, phytochemistry and biological activities - Anh, Nguyen Hoang; Park, SeonJu; Trang, Do Thi; Yen, Duong Thi Hai; Tai, Bui Huu; Yen, Pham Hai; Kiem, Phan Van; Chinh, Pham The; Nhiem, Nguyen Xuan (Vietnam Journal of Science and Technology, 2022)
Ethnopharmacological relevance: The genus Mallotus (Euphorbiaceae family) includes 124 accepted names and distributes in tropical and sub-tropical regions. Some Mallotus species are used in traditional medicines for the treatment of chronic hepatitis, enteritis stomach, disorders, cholelithiasis, anti-cancer, gastric, and duodenal ulcers. Aim of the study: According to the Scifinder database, this is the first review study that focuses on the phytochemistry and pharmacology of Mallotus genus (17 Mallotus species) to understand the link between the traditional medicinal uses, phytochemistry, and bioactivities. Thus, they provides a scientific fundamental for further research in the phytochemical and pharmacological activities of their species. Materials and methods: Information about the Mallotus genus was collected using various databases, such as Web of Science, SciFinder, PubMed, Sci-hub, Google Scholar, Wiley, Elsevier, ACS publications, and SpringerLink between 1978 and 2021. Plant names were validated by “The Plant List” (www.theplantlist.org). Results: Up to now, total 325 compounds were reported from Mallotus species, including phloroglucinols, steroids, coumarins, benzopyrans, flavonoids, chalcones, galics, and bergenins. The extracts and phytochemical constituents of the Mallotus genus are a rich source of biologically active, including anti-cancer, anti-inflammatory, immunoregulatory, antioxidant, antibacterial, antifungal, anti-virus, and other activities. Conclusions: The review indicated that the Mallotus genus is a promising source of biological activities compounds, special anti-cancer chromanes. The results of this review confirm the great potential of Mallotus species. Thus, it will be helpful for further research in the phytochemistry and pharmacology of the Mallotus genus.